Contextual Multicultural Education: Exploring Local Values in Multiethnic Societies - Rintia Rintia; Wilodati Wilodati; Bunyamin Maftuh (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2025)
This study aims to examine the implementation of multicultural education based on local values in the multiethnic community of Kayu Aro. Kayu Aro is home to various ethnic groups, including Kerinci, Javanese, Minangkabau, and Batak, who have long coexisted in shared social, cultural, and economic spaces. Although this diversity has given rise to harmonious social practices such as interethnic cooperation, tolerance toward cultural traditions, and the use of Javanese as a lingua franca, these values have not yet been systematically integrated into the formal educational process. As a result, lessons on diversity in schools often remain abstract and detached from the students’ lived experiences. This research adopts a mixed methods approach, with concurrent triangulation design. Qualitative data were collected through in-depth interviews and field observations, while quantitative data were obtained through student surveys measuring their understanding of multicultural values. The findings show that local values possess strong potential to serve as a foundation for multicultural education, particularly in fostering students’ awareness of the importance of coexistence in a plural society. However, the absence of structured efforts to incorporate these local narratives into school curricula and teaching strategies remains a significant barrier. This study recommends the integration of local values into school practices as a contextualized and culturally responsive approach to multicultural education one that is equitable, experience-based, and rooted in the social realities of students.Keywords: Multicultural Education, Local Values, Multiethnic Society, Contextual Learning